Injectable Mesocellular Foam Silica Microparticles with a Dual Role of Cell-Recruiting Scaffolds and Intracellular Delivery Vehicles for Enhanced Cancer Vaccine - Im, Jihye; Choi, Youngjin; Nguyen, Thanh Loc; Kim, Min Kyung; Kim, Jaeyun (John Wiley & Sons Ltd., 2024)
The cancer vaccine is one of the potent cancer immunotherapies based on provoking antigen-specific adaptive immune responses in patients. Activating host antigen-presenting cells by delivering antigens and adjuvants is one of the most important requirements to enhance cancer vaccine efficacy. This study proposes an effective cancer vaccine platform based on injectable mesocellular foam (MCF) silica microparticles with a dual role capable of in situ recruitment of host dendritic cells (DCs) and intracellular delivery of antigens to the recruited DCs. Subcutaneously administrated MCF microparticles loaded with chemoattractant to DCs (GM-CSF), antigenic protein (OVA), and TLR9 agonist (CpG-ODN) lead to robust DC maturation and high antigen-specific T cell responses. The cell recruitment, DC activation, and T cell responses of MCF-based cancer vaccine are significantly higher than injectable mesoporous silica scaffold, of which role is mostly limited to the cell recruiting scaffold. These features of MCF lead to effective inhibition of tumor growth in prophylactic vaccine setting and lung metastatic cancer model, representing MCF enabling cell-recruiting scaffold formation and intracellular delivery of antigen can be a promising material platform for an enhanced cancer vaccine. Injectable mesocellular foam silica (MCF) microparticles successfully perform a dual role capable of in situ dendritic cells (DCs) recruitment and intracellular delivery of antigens to the recruited DCs. Subcutaneously administrated MCF loaded with chemokine, antigen, and adjuvants leads to DC maturation and high antigen-specific T cell responses, effectively inhibiting tumor growth in subcutaneous tumor model and lung metastatic model.image